2016
DOI: 10.1128/jvi.01464-15
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Enhanced Vaccine Cell Lines To Eradicate Vaccine-Preventable Diseases: the Polio End Game

Abstract: Vaccine manufacturing costs prevent a significant portion of the world's population from accessing protection from vaccinepreventable diseases. To enhance vaccine production at reduced costs, a genome-wide RNA interference (RNAi) screen was performed to identify gene knockdown events that enhanced poliovirus replication. Primary screen hits were validated in a Vero vaccine manufacturing cell line using attenuated and wild-type poliovirus strains. Multiple single and dual gene silencing events increased poliovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 38 publications
3
51
1
1
Order By: Relevance
“…While others were unsuccessful in propagating HuNoV in Vero cells [38,44,45], we show that low-passed Vero cells can be used as a cell substrate for HuNoV. We previously used low-passaged Vero cells in the development of vaccine substrates for several viruses [52,54]. To begin to evaluate HuNoV infection, we showed that HuNoV RNAs are present within Vero cells following a 1 h or 6 h incubation by qRT-PCR ( Figure 1A).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…While others were unsuccessful in propagating HuNoV in Vero cells [38,44,45], we show that low-passed Vero cells can be used as a cell substrate for HuNoV. We previously used low-passaged Vero cells in the development of vaccine substrates for several viruses [52,54]. To begin to evaluate HuNoV infection, we showed that HuNoV RNAs are present within Vero cells following a 1 h or 6 h incubation by qRT-PCR ( Figure 1A).…”
Section: Resultsmentioning
confidence: 82%
“…To elucidate some of the antiviral Vero cell genes that modify HuNoV replication, we evaluated siRNA knockdown (KD) of host genes previously identified to be important for influenza virus [76], poliovirus [54], and rotavirus [53] replication. KD of several genes in Vero cells, specifically empty spiracles homeobox 2 (EMX2), fibroblast growth factor 2 (FGF2), neuraminidase 2 (NEU2), pyrroline-5carboxylate reductase 1 (PYCR1), RAD51 associated protein 1 (RAD51AP1), and Sec61 translocon gamma subunit (SEC61G) enhanced HuNoV replication in Vero cells ( Figure 5 and Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR/Cas9 technologies also offer the potential to overcome some of our present obstacles in vaccine development, and novel strategies have improved yield and efficiency of vaccine manufacturing (Tang et al, 2016;van der Sanden et al, 2016;Yuan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Phase I, a total of 23 proposals were accepted, and 3 projects were selected for Phase II. The projects selected for Phase II included intense continuous polio surveillance in China (Dr. Yong Zhang) (55), establishment of new highproducing cell lines for a PV vaccine (Dr. Ralph Tripp) (56), and increasing production capacity of empty PV capsids (Dr. Ian Jones) for affordable IPV. We might see a down-to-earth way of the Foundation in the selection of PV studies, but innovation, in terms of drastic breakthroughs for the eradication program endgame, has been limited.…”
Section: Pv Study Supported By Who and The Bill And Melinda Gates Foundmentioning
confidence: 99%
“…Major basic studies of PV in the endgame of polio eradication can slightly decrease or increase the resulting neutralizing antibody titer, depending on the PV serotypes, but its actual effectiveness in the suppression of wild PV circulation remained to be verified. Development of engineered knock-out cell lines might increase the PV yield of for IPV production (56). Hyper-attenuated strains have been developed by adaptation of PV to cold temperatures (58), or by modification of the RNA stem-loop in the PV-IRES (59).…”
Section: Overview Of Ongoing Pv Studies In the Polio Endgamementioning
confidence: 99%